LEGAL PROTECTION OF LABOR RIGHTS DURING THE CORONAVIRUS DISEASE 2019 (COVID-19) PANDEMIC - Sholahuddin Al-Fatih; Fachry Ahsany; Ahmad Faiz Alamsyah (UNISSULA, 2020)
Since the Coronavirus Disease 2019 (Covid-19) pandemic in Indonesia, which continues to grow and has an impact, not a few companies have gone bankrupt. Whether it's a small company, a medium-sized company or even a large corporation are affected by the Coronavirus Disease 2019 (Covid-19). This paper aims to find legal issues on labor right during Covid-19 pandemic in Indonesia. Using the normative legal research, this paper analyzess some of regulation and legal government act to protect labor right who terminated (Pemutusan Hubungan Kerja/PHK) during Covid-19 pandemic. In the end, this paper finds that the government issued two program to solve PHK and protect labor rights, namely Pre-Works Card and Cash Incentive Program (Bantuan Langsung Tunai/BLT). It actively helps employee to create a new job and continue their daily life.